2018
DOI: 10.1002/jcla.22626
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between auditory‐vestibular functions and estrogen levels in postmenopausal patients with Meniere's disease

Abstract: Estrogen levels correlated with auditory and vestibular function in postmenopausal patients with MD. Low estrogen may be involved in the microcirculatory disturbance of the inner ear, affecting the occurrence and development of MD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Several reports had revealed a slight female preponderance in Meniere’s disease [ 54 , 55 ]. Those who had a lower estrogen level presented poor auditory function in postmenopausal patients with Meniere’s disease [ 56 ]. Autoimmune inner ear disease features fluctuating bilateral progressive sensorineural hearing loss within weeks or months, likely due to a consequence of antibodies from various conditions such as viral infection, trauma, and vascular injury that damaged the inner ear [ 57 ].…”
Section: Clinical Aspects Of Sex Differences In Acquired Sensorineural Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports had revealed a slight female preponderance in Meniere’s disease [ 54 , 55 ]. Those who had a lower estrogen level presented poor auditory function in postmenopausal patients with Meniere’s disease [ 56 ]. Autoimmune inner ear disease features fluctuating bilateral progressive sensorineural hearing loss within weeks or months, likely due to a consequence of antibodies from various conditions such as viral infection, trauma, and vascular injury that damaged the inner ear [ 57 ].…”
Section: Clinical Aspects Of Sex Differences In Acquired Sensorineural Hearing Lossmentioning
confidence: 99%
“…Therefore, estrogen may play an important role in maintaining hearing and balance. For example, estrogen levels correlated with auditory and vestibular function in postmenopausal patients with Meniere’s disease [ 56 ] because lower estrogen may be involved in the microcirculatory disturbance and endolymphatic hydrops of the inner ear [ 117 ].…”
Section: How Could Hormones Influence Hearing In Molecular Aspects?mentioning
confidence: 99%
“…Moreover, it has been shown that the low estrogen levels noted in postmenopausal women may cause microcirculatory disorders in the inner ear, leading to the development of MD ( 7 ). Consequently, the present study indicated that the benefits obtained by postmenopausal women with MD using DRSP/E2 treatment may be due to the type, dosage, combination and regimen of progestogen and E2.…”
Section: Discussionmentioning
confidence: 99%
“…DRSP derived from 17a-spironolactone is a progestin with an important antimineralocorticoid activity, which is able to reduce salt and water retention and to exert diuretic and anti-edema effects (11). Moreover, it has been shown that the low estrogen levels noted in postmenopausal women may cause microcirculatory disorders in the inner ear, leading to the development of MD (7). Consequently, the present study indicated that the benefits obtained by postmenopausal women with MD using DRSP/E2 treatment may be due to the type, dosage, combination and regimen of progestogen and E2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation